Collaborative discipline for at-risk students - Byers, George H. (West Nyack, N.Y. : Center for Applied Research in Education, 1994)
Bonding. Communication. Problem solving. Career/leisure activities. Parent support program. Transitional planning.
Keywords: Education; Discipline; Peer counseling of students -- United States; School discipline -- United States; Behavior modification -- United States